2020
DOI: 10.1128/jvi.01215-20
|View full text |Cite
|
Sign up to set email alerts
|

The BHLF1 Locus of Epstein-Barr Virus Contributes to Viral Latency and B-Cell Immortalization

Abstract: The Epstein-Barr virus (EBV) BHLF1 gene encodes an abundant linear and several circular RNAs believed to perform non-coding functions during virus replication, though an open reading frame is retained among an unknown percentage of EBV isolates. Evidence suggests that BHLF1 is also transcribed during latent infection, which prompted us to investigate the contribution of this locus to latency. Analysis of transcripts transiting BHLF1 revealed its transcription is widespread among B-cell lines supporting the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 81 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have indicated that the BHLF1 gene encodes several circular and a large number of linear RNAs that play non-coding roles during virus replication [ 34 , 35 ]. However, Yetming et al recently demonstrated that BHLF1 is also transcribed during latency and may function mainly instead via its transcript as a lncRNA to contribute to viral latency and B cell immortalization [ 36 ]. However, the specific role of BHLF1 lncRNA in tumourigenesis is still not clear.…”
Section: Ebv-encoded Lncrnas In the Latent Phasementioning
confidence: 99%
“…Previous studies have indicated that the BHLF1 gene encodes several circular and a large number of linear RNAs that play non-coding roles during virus replication [ 34 , 35 ]. However, Yetming et al recently demonstrated that BHLF1 is also transcribed during latency and may function mainly instead via its transcript as a lncRNA to contribute to viral latency and B cell immortalization [ 36 ]. However, the specific role of BHLF1 lncRNA in tumourigenesis is still not clear.…”
Section: Ebv-encoded Lncrnas In the Latent Phasementioning
confidence: 99%
“…circBHLF1 is derived from the intra-exonic backsplicing of the BHLF1 gene (Toptan et al, 2018;Ungerleider et al, 2018). Increasing evidence has indicated that BHLF1 can be expressed in both latency and lytic cycles and may work as a non-coding gene for various EBV strains (Lin et al, 2010(Lin et al, , 2013Yetming et al, 2020). The expression level of circBHLF1 is largely consistent with the isogenic linear transcript and it can be detected in most of the latency and reactivation conditions examined.…”
Section: Bhlf1 Locusmentioning
confidence: 92%
“…In addition, B cells from three out of four donors infected with either deletion demonstrated impaired B cell immortalization when compared to wild-type EBV. Cells from one donor were transformed equally effectively regardless of which of the three viruses were used to infect the cells, although the authors noted that these B cells appeared to be more sensitive to transformation than B cells from other donors [ 108 ]. Notably, the above experiments on B cell transformation were performed in vitro.…”
Section: Overview Of Ebv Latencymentioning
confidence: 99%